Delirium in Critically ill Patients in a Tertiary Care Centre in Western Region of Nepal - Thapa, P; Chakraborty, PK; Khattri, JB; Ramesh, K; Sharma, P (Kathmandu University Medical Journal, 2015)
Background Delirium affects a significant proportion of critically ill patients admitted in hospital. It is associated with various adverse outcomes. Despite its enormous prognostic significance it tends to be underdiagnosed. There is a dearth of studies on risk factors of delirium in our setting. Objectives The main objectives of this study was to find out the prevalence, rate of non recognition and risk factors associated with delirium in hospitalized critically ill patients. Methods A hospital based cross-sectional study was carried out. Data was collected using a predesigned semi-structured proforma and Intensive care delirium screening checklist was used to screen for delirium in patients admitted in various wards of Manipal teaching hospital, Pokhara, Nepal. Results Ninety five cases were included in the analysis. The mean age of study group was 58.9 ± 19.1 years. Delirium was present in 15/95 cases and it was not recognized by treating physician in about one third of cases. Odds ratio (OR) was statistically significantly increased in patients with history of stroke (OR=4.484 95% CI=1.0896;18.459), alcohol use (OR=10.792 95% CI=2.906;40.072), smoking (OR= 4.836 95% CI= 1.411;16.576), use of restraint (OR=17.143 95% CI=4.401;66.766), nasogastric tube placement (OR= 7.731 95% CI=2.348;25.452) and use of Foley’s catheter (OR=12.000 95% CI= 3.072;46.877). Conclusion About 16% of critically ill patients were found to be delirious. In about one third of the cases delirium was not recognized. Both patient related and iatrogenic factors may increase the risk of delirium in hospitalized critically ill patients. Kathmandu University Medical Journal Vol.12(2) 2014: 117-120